PENGEMBANGAN MULTIMEDIA GAME PETUALANGAN DALAM LIMAS BERBASIS MOBILE LEARNING DI KELAS VIII SMP - Ukhti Nurfajriah Sasmita Ijonu (Universitas Tanjungpura, 2022)
This study aimed at developing a multimedia adventure on mobile learning based game in pyramids (PDL) at class VIII. This study used a four-D development model but at the deployment stage, only limited deployment was carried out. This means that the distribution was only carried out in research schools. The subjects in this study were class VIII students of SMP Negeri 1 Tilango Kab. Gorontalo. The results of the study based on the validation of the material experts and media experts showed that the quality of multimedia was good. Meanwhile, based on the teacher's ability to manage learning it was also categorized as good. Students’ activities during the learning process reach the ideal time criteria, the responses of all students are classified as very positive with percentage of 90.56% and students’ learning outcomes tests showed that 72.5% of students achieved completeness. This shows that the multimedia adventure on mobile learning based game in Pyramids(PDL) is good and valid to be used as a learning medium for the pyramid material in class VIII.